2021
DOI: 10.1016/s2468-2667(20)30287-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic inequalities in health-related quality of life among older adults in England: secondary analysis of a national cross-sectional survey

Abstract: Background The population of older adults (ie, those aged ≥55 years) in England is becoming increasingly ethnically diverse. Previous reports indicate that ethnic inequalities in health exist among older adults, but information is limited by the paucity of data from small minority ethnic groups. This study aimed to analyse inequalities in healthrelated quality of life (HRQoL) and five determinants of health in older adults across all ethnic groups in England. MethodsIn this cross-sectional study, we analysed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 18 publications
4
99
0
Order By: Relevance
“…BAME participants were also significantly less likely to download the app to help the NHS. A recent study on health-related quality of life revealed inequalities within English ethnic minorities [ 36 ], including poor primary care experiences, inadequate support from local services, and low patient self-confidence. This indicates that government slogans like “protect the NHS” may not have the intended effect on BAME communities and should be rethought to be more inclusive.…”
Section: Discussionmentioning
confidence: 99%
“…BAME participants were also significantly less likely to download the app to help the NHS. A recent study on health-related quality of life revealed inequalities within English ethnic minorities [ 36 ], including poor primary care experiences, inadequate support from local services, and low patient self-confidence. This indicates that government slogans like “protect the NHS” may not have the intended effect on BAME communities and should be rethought to be more inclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of many long-term health conditions is greater in some ethnic minority populations and deprived communities which may also be a factor. 17–19 One survey, based on data up to the end of January 2021, found 51.9% of the of the population did not seek help for a worsening health condition during the pandemic. 20 Long-term conditions have very different treatment pathways and the wider impact of the pandemic may not be the same for all.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of many long-term health conditions is greater in some ethnic minority populations and deprived communities which may also be a factor (17-19). One survey, based on data up to the end of January 2021, found 51.9% of the of the population did not seek help for a worsening health condition during the pandemic (20).…”
Section: Discussionmentioning
confidence: 99%